166k views
3 votes
Simplify each expression. Write your answer without negative exponents.

Simplify each expression. Write your answer without negative exponents.-example-1
Simplify each expression. Write your answer without negative exponents.-example-1
Simplify each expression. Write your answer without negative exponents.-example-2

1 Answer

3 votes

16)

s^1/4 * s^1/4 * s^1/4 * s^1/4 = s^(1/4 + 1/4+1/4+1/4) = s^4/4 = s

Answer is s

15) Answer is 1. (because any number to the 0 exponent is equal 1 , except 0)

17)

= (t^3/6)^2 = t^6/6 = t

Answer is t


User Nikoliazekter
by
5.3k points